Microbial Profiling of a Suppressiveness-Induced Agricultural Soil Amended with Composted Almond Shells - Vida, Carmen; Bonilla, Nuria; de Vicente, Antonio; Cazorla, Francisco M. (Frontiers in Microbiology, 2016)
This study focused on the microbial profile present in an agricultural soil that becomes suppressive after the application of composted almond shells (AS) as organic amendments. For this purpose, we analysed the functions and composition of the complex communities present in an experimental orchard of forty-year-old avocado trees, many of them historically amended with composted almond shells. The role of microbes in the suppression of Rosellinia necatrix, the causative agent of avocado white root rot, was determined after heat-treatment and complementation experiments with different types of soil. Bacterial and fungal profiles obtained from natural soil samples based on the 16S rRNA gene and ITS sequencing revealed slight differences among the amended (AS) and unamended (CT) soils. When the soil was under the influence of composted almond shells as organic amendments, an increase in Proteobacteria and Ascomycota groups was observed, as well as a reduction in Acidobacteria and Mortierellales. Complementary to these findings, functional analysis by GeoChip 4.6 confirmed these subtle differences, mainly present in the relative abundance of genes involved in the carbon cycle. Interestingly, a group of specific probes included in the “soil benefit” category was present only in AS-amended soils, corresponding to specific microorganisms previously described as potential biocontrol agents, such as Pseudomonas spp., Burkholderia spp. or Actinobacteria. Considering the results of both analyses, we determined that AS-amendments to the soil led to an increase in some orders of Gammaproteobacteria, Betaproteobacteria and Dothideomycetes, as well as a reduction in the abundance of Xylariales fungi (where R. necatrix is allocated). The combination of microbial action and substrate properties of suppressiveness are discussed.